ALAT BANTU MATRAS UNTUK PEMBELAJARAN SENAM GULING DEPAN DAN BELAKANG BAGI SISWA KELAS ATAS SEKOLAH DASAR - SYAM, ASRY; YASIN , ISMET; SYAHRUDDIN, SYAHRUDDIN (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2024)
Floor exercise lessons, especially front and back tumbling, are not easy for elementary school students. Changing from stability to imbalance by rolling over is not a familiar activity. The aim of this research is to develop tools to make it easier for students to learn front and back rolls. The research method uses the ADDIE development model. The initial product test on a small scale was 16 class V students at SDN 89 Sipatana, Gorontalo City and on a large scale it was 20 class V students at SDN 96 Kota Utara. Data collection through expert validation and student questionnaires as an evaluation of product feasibility, research results of tilting mattress product tests in the "Small Scale" category reached a percentage of 73.55% of the "Feasible" criteria, while the "Small Scale" category. Large Scale" achieved a percentage of 73.68% of the "Feasible" criteria. On the scale of feasibility of floor exercise roll learning media. The development of learning media on floor exercise roll materials using sloping mats for elementary school students was successful. This media has been proven to make a contribution in creating a more conducive and effective learning environment for students. ABSTRAKPelajaran senam lantai khususnya guling depan dan belakang menjadi hal yang tidak mudah bagi siswa sekolah dasar. Perubahan dari stabil ke ketidakseimbangan dengan berguling bukan menjadi aktivitas yang famiiier. Tujuan penelitian ini untuk menyusun alat untuk memudahkan siswa belajar guling depan dan belakang. Metode penelitian dengan mengunakan Model pengembangan ADDIE. Uji produk awal skala kecil adalah 16 orang siswa kelas V di SDN 89 Sipatana Kota Gorontalo dan skala besar adalah 20 orang siswa kelas V di SDN 96 Kota Utara. Pengumpulan data melalui kuisioner siswa sebagai evaluasi kelayakan produk, Hasil Penelitian uji produk matras miring dalam kategori "Skala Kecil" mencapai presentase 73,55% kriteria “Layak” sedangkan "Skala Besar" mencapai presentase 73,68% kriteria "Layak". Dalam skala kelayakan media pembelajaran roll senam lantai. Pengembangan media pembelajaran pada materi roll senam lantai dengan menggunakan matras miring pada siswa sekolah dasar berhasil. Media ini telah terbukti memberikan kontribusi yang dalam menciptakan lingkungan pembelajaran yang kondusif dan efektif bagi siswa dengan lebih baik.